Perbedaan Hasil Belajar Sejarah Peserta Didik di SMA Negeri 4 Solok Berdasarkan Pola Asuh Orang Tua - Nilam Insani Mukhlisa; Wahidul Basri (Jurnal Halaqah, 2021)
This study aims to find out the difference in historical learning outcomes based on parental parenting. This research is quantitative research with a type of comparative study research. The research population as well as being a sample of research is all students of class XI IPS at Sma Negeri 4 Solok. Data collection techniques use Questionnaires to obtain parenting data and documentation to obtain data on historical learning outcomes. The data was analyzed using the Anova test. The results showed that the results of learning the history of learners using democratic parenting were most dominant and had a higher average score than other parenting, which was 79.74. In addition, hypothesis testing showed Fhitung = 6,855 and Ftabel 3.15. Or Fhitung > Ftabel so that the hypothesis is accepted. It can be concluded that there are differences in the results of learning the history of learners based on Parenting Parents at State High School 4 Solok.